Development of the high-strength ductile ferritic alloys via regulating the intragranular and grain boundary precipitation of G-phase. (10th February 2023) - Yang, Mujin; Huang, Chao; Han, Jiajia; Wu, Haichen; Zhao, Yilu; Yang, Tao; Jin, Shenbao; Wang, Chenglei; Li, Zhou; Shu, Ruiying; Wang, Cuiping; Lu, Huanming; et al.
Highlights: Although the nano-dispersed precipitation of G-phase within the grain hardens the alloy remarkably, its large amount of precipitation at the grain boundary leads to serious alloy embrittlement. For the first time, the crystal structure transition of nano-dispersed precipitates from the Fe2 TiSi-L21 to the Ni16 Ti6 Si7 -G phase is observed within the ferrite at the early stage of aging. Guided by current TEM and DFT results, the interfacial energy is predicted to play a leading role in forming the cube-on-cube orientation relationship between α-Fe and G-phase. Adopting the "cold-rolling and aging" process to effectively avoid its precipitation at grain boundaries, a class of high-performance ferroalloys with both high strength and good ductility is realized. Abstract: A typical G-phase strengthened ferritic model alloy (1Ti:Fe-20Cr-3Ni-1Ti-3Si, wt.%) has been carefully studied using both advanced experimental (EBSD, TEM and APT) and theoretical (DFT) techniques. During the classic "solid solution and aging" process, the superfine (Fe, Ni)2 TiSi-L21 particles densely precipitate within the ferritic grain and subsequently transform into the (Ni, Fe)16 Ti6 Si7 -G phase. In the meanwhile, the elemental segregation at grain boundaries and the resulting precipitation of a large amount of the (Ni, Fe)16 Ti6 Si7 -G phase are also observed. These nanoscale microstructural evolutions result in a remarkable increase in hardness (100–300 HV) and severe embrittlement. When the "cold rolling and aging" process is used, the brittle fracture is effectively suppressed without loss of nano-precipitation strengthening effect. Superhigh yield strength of 1700 MPa with 4% elongation at break is achieved. This key improvement in mechanical properties is mainly attributed to the pre-cold rolling process which effectively avoids the dense precipitation of the G-phase at the grain boundary. These findings could shed light on the further exploration of the precipitation site via optimal processing strategies. Graphical abstract: Image, graphical abstract